Accidental hypothermia in recreational activities in the mountains: A narrative review. (1st October 2018) - Procter, Emily; Brugger, Hermann; Burtscher, Martin
Abstract : The popularity of recreational activities in the mountains worldwide has led to an increase in the total number of persons exposed to cold and extreme environments through recreation. There is little conclusive evidence about the risk of hypothermia for specific activities or populations, nor is it clear which activities are represented in the literature. This is a non‐systematic review of accidental hypothermia in different recreational activities in the mountains, with a specific focus on outdoor or winter activities that potentially involve cold exposure. Cases of hypothermia have been reported in the literature in mountaineering, trekking, hiking, skiing, activities performed in the backcountry, ultra‐endurance events, and databases from search and rescue services that include various types of recreation. Of these activities, hypothermia as a primary illness occurs most commonly during mountaineering in the highest elevation areas in the world and during recreation practiced in more northern or remote areas. Hypothermia in skiers, snowboarders, and glacier‐based activities is most often associated with accidents occurring off‐piste or in the backcountry (crevasse, avalanche). Organizers of outdoor events also have a role in reducing the incidence of hypothermia through medical screening and other preparedness measures. More complete collection and reporting of data on mild hypothermia and temperature measurement would improve our understanding of the incidence of hypothermia in outdoor recreation in future.